2002
DOI: 10.1021/ac0203544
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrochemical Properties of Optically Transparent, Boron-Doped Diamond Thin Films Deposited on Quartz

Abstract: The optical and electrochemical properties of transparent, boron-doped diamond thin film, deposited on quartz, are discussed. The films were deposited by microwave-assisted chemical vapor deposition, for 1-2 h, using a 0.5% CH4/H2 source gas mixture at 45 Torr and 600 W of power. A high rate of diamond nucleation was achieved by mechanically scratching the quartz. This pretreatment leads to the formation of a continuous film, in a short period of time, which consists of nanometer-sized grains of diamond. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 21 publications
7
91
0
Order By: Relevance
“…In the other architecture, a thin film is deposited on an optically transparent substrate; for example, a diamond/quartz OTE (24,26). This OTE is analogous to a thin film of ITO on quartz and has an electric resistivity of ~10 S/cm, an optical transparency of ~50% at 300-800 nm, a working-potential window of ≥3V in aqueous media, stable voltammetric background currents and optical properties over a wide potential range, and relatively rapid electron-transfer kinetics for a number of redox systems without conventional pretreatment.…”
Section: Sp 3 -Bonded Carbon Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other architecture, a thin film is deposited on an optically transparent substrate; for example, a diamond/quartz OTE (24,26). This OTE is analogous to a thin film of ITO on quartz and has an electric resistivity of ~10 S/cm, an optical transparency of ~50% at 300-800 nm, a working-potential window of ≥3V in aqueous media, stable voltammetric background currents and optical properties over a wide potential range, and relatively rapid electron-transfer kinetics for a number of redox systems without conventional pretreatment.…”
Section: Sp 3 -Bonded Carbon Electrodesmentioning
confidence: 99%
“…strated on the optically active redox systems ferri/ferrocyanide and methyl viologen with a freestanding diamond disk OTE (22). This was followed by work on the optically active redox molecule chlorpromazine with a diamond/quartz OTE (24).…”
Section: Uv-vis Measurementsmentioning
confidence: 99%
“…Currently, diamond devices are used in high power electronics [2], diamond diodes [3], high-power switches [4] or high-frequency devices, such as transistors [5]. However, the most common use of BDD materials is for electrodes in electrochemistry [6][7][8] or spectroelectrochemistry [9]. The electrodes of this type have a good chemical and electrochemical stability even in highly aggressive media, a long lifetime and a wide potential window for the water discharge.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that an area of the high conductivity density correlates with a high boron doping level along with electrical conductivity heterogeneity of boron-doped poly-/microcrystalline diamond surfaces. Stotter et al [9] investigated an optical transmittance in the UV-VIS range and absorbance with a spectro-electrochemistry method based on measurements using an optical transparent BDD electrode with a maximum 50% transmittance on quartz. These results showed that the optical and electrical properties were extremely stable during 48-h exposure tests in various aqueous (HNO3, NaOH) solutions and non-aqueous (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation